Impact of Swollen Shoot Disease on the Livelihoods of Smallholder Cocoa farmers in Côte d'Ivoire - Adopo, Wenceslas Affessi; Adolphe, Mahyao Germain; Tiehi, Nestor; Koffi, Camille; Kouakou, Koffie; Ballo, Zié (European Scientific Journal, ESJ, 2022)
The Cocoa Swollen Shoot Disease (CSSD) due to badnavirus species is endemic in West Africa and caused significant and irreversible economy losses for smallholder cocoa farmers in infected areas in Ghana and Côte d’Ivoire. The impact of the disease on the small farmers livelihoods has been investigated at cocoa farm households level in Côte d‘Ivoire. For that, the propensity score matching method was used to construct a counterfactual and to compair group capturing the situation of affected households before the disease occuring on their plantation, based on the observable characteristics of non affected households. A total of 800 cocoa farmers were randomly interviewed using a semi-structured questionnaire. Results shown significant differences of expenditures for children's schooling and health of household’s with plantations infected by the disease compared to non affected. It was also found that households with swollen shoot in their cocoa plantation use less modern health services and invest less in children's education.